2022
DOI: 10.1017/s1352465822000145
|View full text |Cite
|
Sign up to set email alerts
|

South African youth’s understanding of feelings, thoughts and behaviours: Implications for the development of CBT-based mental health interventions

Abstract: Background: Mental health problems are common in youth in low- and middle-income countries (LMICs), including South Africa. Preventative interventions, based on cognitive behaviour therapy (CBT), delivered in schools, have been found to alleviate symptoms of depression and anxiety in high income countries (HICs). However, less is known about whether youth in LMICs are able to engage with the core concepts of CBT. Aims: To explore how young people in the Western Cape, South Africa, unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Time constraints for intervention delivery were particularly salient in our second school when intervention delivery took place close to exam time. We specifically developed 4STMF based on detailed stakeholder work (Coetzee, Gericke, Human, Stallard, & Loades, 2022 ; Human, Gericke, Loades, Stallard, & Coetzee, 2022 ), which endorsed the need for this sort of programme. Based on the work reported here, we have found that 4STMF is both feasible and acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Time constraints for intervention delivery were particularly salient in our second school when intervention delivery took place close to exam time. We specifically developed 4STMF based on detailed stakeholder work (Coetzee, Gericke, Human, Stallard, & Loades, 2022 ; Human, Gericke, Loades, Stallard, & Coetzee, 2022 ), which endorsed the need for this sort of programme. Based on the work reported here, we have found that 4STMF is both feasible and acceptable.…”
Section: Discussionmentioning
confidence: 99%